Diagnosis of Dry Eye Syndrome During the Preparing Patients for Cataracts Phacoemulsification. Literature Review - V. N. Trubilin; E. G. Polunina; A. V. Trubilin; V. V. Kurenkov; M. E. Konovalov; V. S. Zakatianskii (Oftalʹmologiâ)
The increasing patient demands for quality of life after surgery necessitate optimization of approaches in the field of surgical intervention, reduction of the frequency of refractive errors and correction of tactics of postoperative interventions. Literature data indicate that refractive errors are possible after surgical treatment for cataracts associated with the presence of dry eye syndrome in the preoperative period. Tear film is used as the first refractive medium, and the size of the refractive change at airtear film interfaces is the most innovative of any interface in any other optical system. Thus, changes of tear film physiology affect overall vision with higher order aberrations and irregular astigmatism occurring. The presented literature review analyzes data from scientific studies aimed at studying risk factors for the development of dry eye syndrome and diseases associated with it when phacoemulsification of cataracts occurs. Considering the fact that, according to various studies, the incidence of dry eye syndrome after cataract surgery ranges from 9.8 to 96.6% in cataract surgery in collaboration with dry eye surgery, adequate approaches within the framework of preoperative preparation are an urgent development. The lack of clear recommendations for effective preoperative screening and respiratory preparation for surgery, unreliable biometric data, and lack of treatment strategy for postoperative dry eye syndrome are indicators of detectors to obtain the desired results. Adequate diagnosis and preparation of ocular surfaces before biometric measurements can reduce refractive errors after surgery.